Management of the Blind Eye and Options for Cosmesis (Canadian Eye Care Today, 2023)
As ophthalmologists, our ultimate goal in the treatment of patients with eye conditions is the preservation of vision and the eye. However, there are conditions necessitating the removal of an eye for pain control; control of infection source; treatment of malignancy; severe trauma; perforated corneal ulcer; or cosmesis. Over the years, there has been a shift in both surgical techniques and choice of implants, all with the goal to improve cosmesis outcome and decrease implant exposure and extrusion. However, there remains a wide range of approaches due to the variety of patient and disease factors. We present here an overview for how to think through the different aspects of eye removal and the subsequent cosmetic rehabilitation.